THE MORAL POWER OF WOMAN: A STUDY OF GANDHI’S ETHICAL HUMANISM (Western European Journal of Historical Events and Social Science, 2025)
If we look at the ancient history of India, while women played an important role in some aspects of this society, the attitude towards them varied from time to time. Mahatma Gandhi highlighted the issue of women because some of the flaws in society violated women’s rights and treated women secondarily. He believed that strengthening the role of women in society for the future of India was a sign of progress